Fear of humans drives complex changes in predators and prey in South Africa - Lasky, Monica, author; Bombaci, Sara, advisor; Berger, Joel, committee member; Smith, Melinda, committee member (Colorado State University. Libraries, 2022)
Wildlife responses to human presence vary greatly; species can be fearful of humans or habituate to human presence. Using experimental and observational methods, I investigated how South African wildlife altered species-specific behavior and predator-prey co-occurrence in response to simulated and actual human presence. I used camera traps to capture wildlife responses to human voice playbacks in areas with and without tourists, and found that wildlife variably altered space use, temporal activity, and fleeing behavior in response to human voice playbacks and tourism, which further altered predator-prey co-occurrence within the system. Human-induced fear elicited a different response from wildlife than predator-induced fear, suggesting that not all species treat humans as they would their natural predators. Furthermore, prey responded to human voice playbacks and tourists similarly, while predators had different responses to human playbacks than how they responded to tourists. Prey species may be using humans as a shield against predation regardless of the amount of time humans have been present within the system, while predators may be more fearful of a novel human stimulus but appeared to be habituated to long-occurring human presence. The eventual habituation to humans by predators reverted the initial decrease in predator-prey co-occurrence to that observed in the control sites, suggesting that eventual habituation of predators to humans may help re-establish prey access to predators in disturbed systems. However, habituation may also lead to future human-predator conflict that can impact species conservation. Finally, I conclude by providing future research directions for studying how humans can impact predator-prey interactions.
Keywords: ecology of fear; human-induced fear; species interactions; habituation; Africa; predator-prey dynamics